Multiple Myeloma Presenting as Acute Kidney Failure Secondary to Lambda Light Chain Deposition - Emond-Boisjoly, Marie-Eve; Lemieux-Blanchard, Emilie; Maietta, Antonia; Forté, Stéphanie (Journal of Hematology Research, 2022)
Renal monoclonal immunoglobulin deposition disease (MIDD) is a rare disease defined by deposition of monoclonal light chains and/or heavy chains on basement membranes and vascular walls of the kidney. We describe a case of a 71-year-old woman with kidney failure secondary to monoclonal immunoglobulin deposition disease lambda in association with plasma cell dyscrasia. Her initial serum protein electrophoresis did not demonstrate a monoclonal protein, and classic cast nephropathy was absent on renal biopsy. However, lambda light chain deposits and associated changes confirmed MIDD. She achieved a very good partial response (VGRP) after 8 cycles of CyBorD (cyclophosphamide, bortezomib, dexamethasone) and her kidney function improved. This case highlights the importance of an early diagnostic with renal biopsy to prevent end-stage renal disease. A review of the existing literature and a discussion on the management of the disease is presented.